2018 NASA/ESA Conference on Adaptive Hardware and Systems (AHS) 2018
DOI: 10.1109/ahs.2018.8541464
|View full text |Cite
|
Sign up to set email alerts
|

EvoFIT composite face construction via practitioner interviewing and a witness-administered protocol

Abstract: Police require reliable facial-composite systems to help identify, arrest and convict criminals. Recent developments, however, have allowed newer versions of the EvoFIT composite system to be made available for policing. The outcome is an online (cloudbased) version and a new system called Witness At Home, both using a simpler interface. Here, we formally compare these two versions to establish potential benefits to policing. Two experiments were conducted. In Experiment 1, participants observed a target ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…We also thought it could be beneficial to law enforcement to assess the effectiveness of CR for a novel method of face construction. Recent technological advances have enabled witnesses to construct a composite themselves in their own time (e.g., Martin et al, 2018). This development allows composites to be used in investigations of less serious crime (e.g., minor theft, vandalism and anti-social behaviour), cases where police practitioners may not have the time (e.g., Alison et al, 2013) to interview witnesses to create a composite.…”
Section: Discussionmentioning
confidence: 99%
“…We also thought it could be beneficial to law enforcement to assess the effectiveness of CR for a novel method of face construction. Recent technological advances have enabled witnesses to construct a composite themselves in their own time (e.g., Martin et al, 2018). This development allows composites to be used in investigations of less serious crime (e.g., minor theft, vandalism and anti-social behaviour), cases where police practitioners may not have the time (e.g., Alison et al, 2013) to interview witnesses to create a composite.…”
Section: Discussionmentioning
confidence: 99%
“…With these motivations in mind, we have been assessing selfadministered procedures, both for standalone (non-Internet) and online applications. Using a simple face-recall CI, Martin et al (2018) found that composites were self-constructed after a long delay with naming of about 25% correct. This initial work highlighted the importance of ergonomic processes and, if an online app is used, the need to limit Internet delays.…”
Section: Chapter Summarymentioning
confidence: 99%